Metallomics related to gallium compounds: biochemical and xenobiochemical aspects - Zeno Gârban; Radu Silaghi-Dumitrescu; Gabriela Gârban; Adina Avacovici; Nicoleta Hădărugă; Cornel Baltă; George-Daniel Ghibu; Cristina Bischin; Olga-Alina Rada (Macedonian Journal of Chemistry and Chemical Engineering, 2014)
Issues concerning the chemical compounds studied in the framework of metallomics are of interest both for biochemistry – domain dealing with the metabolization of nutrients and xenobiochemistry – a subsequent domain of biochemistry dealing with the biodegradation of xenobiotics. In this context, reviewed here are in vivo and in vitro data on inorganic and organo-metallic compounds of gallium (Ga), ranging from cellular and molecular biology, to biochemistry and pathobiochemistry, and to pharmacology and related to homeostasis and nutrient degradation.